2017
DOI: 10.1111/hepr.12916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of stereotactic body radiotherapy for elderly patients with hepatocellular carcinoma

Abstract: Stereotactic body radiotherapy can be effective and safe for the treatment of HCC in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Stereotactic body radiation therapy and proton beam therapy have also demonstrated efficacy in HCC, and early results suggest outcomes equivalent to those of TACE with a reduced adverse-effect profile [168][169][170][171][172][173][174][175] . However, high-quality data on stereotactic body radiation therapy and proton beam therapy are lacking and additional studies are needed to define the optimal treatment selection process for locoregional therapy.…”
Section: Transarterial Embolization and Radiotherapymentioning
confidence: 99%
“…Stereotactic body radiation therapy and proton beam therapy have also demonstrated efficacy in HCC, and early results suggest outcomes equivalent to those of TACE with a reduced adverse-effect profile [168][169][170][171][172][173][174][175] . However, high-quality data on stereotactic body radiation therapy and proton beam therapy are lacking and additional studies are needed to define the optimal treatment selection process for locoregional therapy.…”
Section: Transarterial Embolization and Radiotherapymentioning
confidence: 99%
“…Classic photon radiation therapy has rarely been used in HCC because the dose tolerance of normal liver tissue is considerably lower than that necessary for tumor control. Recently, highly conformal radiotherapy, such as stereotactic body radiation therapy (SBRT), has been reported to achieve good control for small HCCs with a tolerable liver dose [ 6 , 7 ]. However, for larger HCCs, photon therapy cannot easily provide adequate coverage of the target without increasing the risk of radiation-induced liver disease [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] For patients with newly diagnosed and recurrent small liver cancer, a large number of recent studies have shown that the local control rate and overall survival rate of SBRT and radical surgery are similar. [24][25][26][27][28][29] The main limitations of conventional SBRT for liver malignancies are dislocation of the treatment target caused by respiratory movement and acute radiation damage to the liver at low and medium levels. Therefore, how to make SBRT with more accurate image guidance technology is the goal constantly pursued in the era of precision radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The overall local control rate can reach 80% to 100%, and the 3‐year survival rate can reach 54% to 70.0% 21‐23 . For patients with newly diagnosed and recurrent small liver cancer, a large number of recent studies have shown that the local control rate and overall survival rate of SBRT and radical surgery are similar 24‐29 . The main limitations of conventional SBRT for liver malignancies are dislocation of the treatment target caused by respiratory movement and acute radiation damage to the liver at low and medium levels.…”
Section: Discussionmentioning
confidence: 99%